User Requirements in Optical Areal Surface Measurements on the development of an Assistance Systems - Hausotte, Tino; Schmidt, Heiko; et al. (Program of XX IMEKO World Congress "Metrology for Green Growth", 2012)
Optical procedures for surface metrology enable an improved inspection of product properties based on plane-oriented parameters. Yet, users in industry still meet many difficulties concerning the application of the new procedures. Thus, in the cooperative project OptAssyst an assistance system is developed to support the performance of surface measurement tasks with optical procedures. To define required support by the system, a user needs analysis has been conducted and typical problems of practical application have been identified. Copyright © (2012) by the International Measurement Federation (IMEKO
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.lfmt.userre
Keywords: Advanced vocational training; Assistance system; Optical surface metrology; User needs analysis